Effects of mole fraction variations and scaling on total variability in InGaAs MOSFETs. (September 2019) - Zagni, Nicolò; Puglisi, Francesco Maria; Pavan, Paolo; Verzellesi, Giovanni
Abstract: Variability is one of the major roadblocks for III-V semiconductors in nanoscale devices, according to the recent International Roadmap for Devices and Systems (IRDS). A particular concern is the detrimental effect of variability of threshold voltage due to channel compositional variations. In this paper, we investigate the impact of this variability source and the effects of scaling on the performance of Dual-Gate-Ultra-Thin-Body (DG-UTB) In0.53 Ga0.47 As MOSFETs. We model mole fraction variations in terms of the Indium content by taking into account the spatial inhomogeneity of the channel and the corresponding bandgap variations, analyzing the effects on threshold voltage variability. We thus define a variability source, i.e., Band Gap Fluctuation (BGF), and we compare the associated variability with the ones from other important sources, namely, Random Dopant Fluctuation (RDF), Work Function Fluctuation (WFF), Body- and Gate-Line Edge Roughness (B-LER and G-LER). We then define three corner cases for mole fraction variations to determine worst-case variability. Finally, the impact of scaling on variability is assessed by comparing results for two technology nodes on the linear and saturation threshold voltage, V T, lin, V T, sat, on-current, I ON, leakage current, I OFF, and linear and saturation sub-threshold slope, SS . We find that although scaling has no impact on BGF-induced V T variability, it increases the total V T, lin variability as well as that for I ON and I OFF .